PENGARUH STATUS SOSIAL EKONOMI DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS V SDN TAMBAKSARI I SURABAYA - Pratiwi, Desi Eka; Prasetya, Nindy Eka (Program Pendidikan Guru Sekolah Dasar Universitas Pakuan, 2019)
This study aimed to determine (1) the effect of socio-economic status on Learning achievement (2) The effect of learning motivation on learning achievement (3) the effect of socio-economic status all together with Learning motivation on learning achievement. The data analysis technique used a simple regression analysis and multiple regression analysis. Furthermore, the prerequisite analysis in the form of Normality test, Linearity test and Multicollinearity test were done before the analysis data was conducted. The results of this study are: (1) There is a positive and significant effect of Socio-Economic Status on Learning Achievement which is indicated by the value of R count = 0.379> R table = 0.254 this variable affects Learning Achievement. (2) There is a positive and significant effect of Learning Motivation on Learning Achievement of Fifth Grade (V) Students of SDN Tambaksari I Surabaya which is indicated by the value of R count = 0.453> R table = 0.254 this affects Learning Achievement. (3) There is a positive and significant effect of Socio-Economic Status all toghether with Learning Motivation on Student Achievement of Fifth Grade (V) Students of SDN Tambaksari I Surabaya which is indicated by the value of R count = 0.543> R table = 0.254 with this jointly influencing Learning Achievement.